Coastal shuttle tanker inventory routing model with a discrete loaded quantity. Issue 53 (14th November 2021) - Xin, Xu; Wang, Xiaoli; Chen, Zigen; Chen, Kang
ABSTRACT: This paper investigates a coastal shuttle tanker inventory routing problem. We convert the problem into a vehicle routing problem with time windows by using the discrete tanker loaded quantity and formulate this problem as an integer programming model. The model aims to minimize the total operating costs of the tanker fleet during the observation period. The composition and scheduling scheme of the fleet and loaded quantity of each tanker are collaboratively optimized. Based on the branch-and-price algorithm framework, an exact algorithm that can solve the actual-scale problem is designed. The efficiency and effectiveness of the algorithm are tested, and a sensitivity analysis is conducted for the fuel cost of the tankers. The results provide managerial insights that are expected to be beneficial for oil companies.